Haemoglobinuria due to hypophosphataemia in last trimester pregnant buffalo - Reddy, B. Soma Sekhar; Reddy, B. Sudhakara; Venkatasivakumar, R.; Sivajothi, S. (International Journal of Biological Research, 2014)
A buffalo in her last trimester pregnancy was referred to clinic with signs of anorexia, voiding dark red coloured urine, dullness, mild diarrhoea and depression. It was diagnosed as an acute case of parturient haemoglobinuria by assessing the serum biochemical parameters. It had low levels of serum protein, albumin and phosphorous. Haemogram revealed decreased erythrocyte count, haemoglobin and haematocrit. The buffalo had been treated with phosphorous supplements and other supportive therapy. Keywords: Buffalo, Last Trimester Pregnancy, Haemoglobinuria, Hypophosphataemia.